Juridical Analysis of Lawsuits Case for Unlawful Acts of the Invalidity of Transfer of Property Rights to Movable Properties - Fathalya Laksana (Law and Justice, 2020)
This study aims to determine the validity of the transfer of property rights to movable property in the context of assets in marriage and the suitability of the judge's decision in his consideration, which states that the Defendant committed an illegal act in the Supreme Court Decision Number 1081K / PDT / 2018. The research method used is a literature study with a normative juridical approach using secondary data in the form of expert opinion and existing theories. This study's findings indicated that the legal basis regarding the transfer of property rights to movable objects in a sale and purchase agreement is regulated explicitly in Article 1457 of the Civil Code. Besides, it is also necessary to pay attention to Article 1320 of the Civil Code regarding the terms of the validity of the agreement and Article 36 of the Marriage Law No. 1 of 1974 concerning the property in marriage. The application of these rules ensures the transfer of property rights to goods being traded, especially the sale and purchase agreement of joint property common in Indonesia. The regulations stipulated in the Civil Code in book 3 concerning engagement, especially regarding sale and purchase agreements, are useful as a guide for the community in taking legal actions in terms of their assets so that they are not mistaken in applying the law. Unlike previous studies, this study focuses more on buying and selling regulations where the sale and purchase object is the property in marriage. Keywords: Sale and Purchase, Actions against the Law, Agreement, Marriage